2014
DOI: 10.1097/maj.0b013e31829bc950
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Function and Self-reported Sleep

Abstract: Background We investigated the relationship between self-reported sleep characteristics and brachial artery flow-mediated dilation (FMD) in a community-based population. Prior studies document that sleep apnea may be related to endothelial dysfunction but disagree whether subjective reports of sleep may also reflect such associations. Methods In 684 subjects (32% male) between 37 and 60 years enrolled in the Emory-Georgia Tech Predictive Health Institute study, we measured reported sleep characteristics usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
1
19
1
Order By: Relevance
“…However, the effects of perceived sleep quality and insomnia in the absence of sleep deprivation on endothelial function are less clear. The lack of association between sleep quality and insomnia score, and brachial artery FMD in our study in a subset of women who slept more than 7 hours/night is in accordance with previous reports where FMD has been mostly unaffected by sleep quality in the absence of curtailed sleep duration 37, 38, 39, 40. We tested mRNA expression of pro‐inflammatory genes ICAM‐1 and VCAM‐1 , which are considered essential for transendothelial migration of monocytes into the arterial wall; however, no significant correlation with perceived sleep quality or ISI score was observed.…”
Section: Discussionsupporting
confidence: 93%
“…However, the effects of perceived sleep quality and insomnia in the absence of sleep deprivation on endothelial function are less clear. The lack of association between sleep quality and insomnia score, and brachial artery FMD in our study in a subset of women who slept more than 7 hours/night is in accordance with previous reports where FMD has been mostly unaffected by sleep quality in the absence of curtailed sleep duration 37, 38, 39, 40. We tested mRNA expression of pro‐inflammatory genes ICAM‐1 and VCAM‐1 , which are considered essential for transendothelial migration of monocytes into the arterial wall; however, no significant correlation with perceived sleep quality or ISI score was observed.…”
Section: Discussionsupporting
confidence: 93%
“…However, only some studies in this review failed to demonstrate such an association 31, 32, 37, 43) and one possible reason for such results could be due to the use of subjective/self-report versus objectively measured sleep parameters to assess the association with subclinical CVD causing biased results. Lauderdale et al found a correlation between self-reported and objectively measured sleep duration of 0.45, which is generally considered as a moderate correlation.…”
Section: Discussionmentioning
confidence: 79%
“…In our study, the elevation of VEGF was significantly promoted by sleep deprivation in rosacea‐like mice, revealing an acceleration in cutaneous angiogenesis. In addition, poor sleep quality was found to be associated with other vasculopathies, such as cerebral small vessel disease 59 and endothelial dysfunction of the brachial artery 60 . VEGF also showed a higher increase with sleep deprivation in a previous study 61 .…”
Section: Discussionmentioning
confidence: 84%